Vibrational spectroscopy - from macro- to nano-world - Matejka P. Pavel; Kral M. Martin; Kokaislova A. Alzbeta; Dendisova M. Marcela; Svecova M. Marie; Jenistová A. Adela; Janousek Jirí J. (Пленарные доклады, 2018)
Заглавие с экрана